Crescimento, pigmentos fotossintéticos e produtividade de cana-de-açúcar (Saccharum sp.), no quarto ciclo de cultivo - Costa, Cicero Teixeira Silva (2009)
The sugarcane (Saccharum officinarum L.) is a species adapted to the tropical climatic conditions and has been presenting fundamental function in the economical development in the Southeast and Northeast regions of the Brasil. The adaptation capacity of the culture to the different cultivation environment can be evaluated through the growth analysis, from the physiologic answers and of the biological and economical production. Thus, the objective of the present work was to evaluate the growth, leaf pigment photosynthetic and yield of four sugarcane varieties (RB92579, SP79-1011, RB931530 and RB93509), in the Tabuleiros Costeiros region, in the State of Alagoas. The work was developed in the experimental area of Centro de Ciências Agrárias, of the Ferderal University of Alagoas in Rio Largo city (09°28'02 ''S; 35°49'43 ''W and altitude de 127m). The statistical design was in random blocks, with four treatments and five replications. They number of plants per meter, stem diameter, plants height, leaf area and leaves area rate (IAF) were evaluated, the measurements began 30 days after the harvest (DAC), except the number of plants that went measured 90 DAC. The leaf pigments photosynthetic were appraised in the period between 213 and 284 DAC. Other evaluations such as: raw material quality, dry mass and yield were evaluated in the harvest period 360 DAC, and the data was submitted to the variance analysis and the averages compared by the Tukey test, with P ≤ 0,05. The results showed that the maximum sprouting happened 90 DAC for all the studied varieties, and the variety RB92579 presented the largest sprouting and the largest stem height in the harvest period. The stem diameter of the RB931530 variety was better than the others, however, it obtained the smallest contents chlorophyll a, b and total and larger correlation (r) between the reading of SPAD-502 and the chlorophylls contents. The RB92579 and BR93509 varieties were better than the others in relation to the sugar production of dry matter and yield, however they differed to each other just to the dry matter. The RB92579 and RB931530 varieties were similar to the soluble solids content (BRIX), percentage of rude sugar (PCC) and recoverable total sugar (ATR).